Juegos didácticos en la enseñanza-aprendizaje de la multiplicación en el tercer grado de la escuela de EGB “Luis Humberto Benítez Costa”, 2021-2022. - Sarango Pasaca, Marlene Liliana (2022)
The didactic game helps to organize a harmonious and favorable environment so that the teaching process is effective, pleasant and at the same time profitable, managing to awaken the students' interest in learning. For this reason, the general objective of this research is to describe the contribution of didactic games in the teaching-learning of multiplication in the third grade of the "Luis Humberto Benítez Costa" GBS school, and for its operationalization, three specific objectives were established, which were: to explain the use of didactic games in the teaching-learning of multiplication, to identify the importance of multiplication in teaching-learning and to establish alternative guidelines on the use of didactic games to improve the teaching-learning of multiplication in students. The type of study was correlational, with a mixed approach and non-experimental design, the methods used were: documentary, hermeneutic and statistical; the techniques: direct observation, survey and interview, with their respective instruments: interview guide, applied to the teacher and pre and post evaluation questionnaire for the students, document based on the contents of the third grade curriculum; the population investigated were the students who make up the school "Luis Humberto Benítez Costa" and by means of a non-probabilistic sampling, the third grade was selected, which is made up of 12 students and 1 teacher. As results, difficulties were evidenced in the learning of multiplication because the methodologies used did not allow teaching the content in a meaningful way, therefore, the proposal "Multiplying efforts to realize dreams" was applied, which contains various activities based on the game, in which an impact of 1.78 points of improvement was obtained; therefore, it is affirmed that didactic games positively influence the assimilation of knowledge and ultimately in the teaching-learning process of multiplication. Keywords: didactic games, importance of games, multiplication, didactic strategy.